The active metabolite of prasugrel inhibits ADP-stimulated thrombo-inflammatory markers of platelet activation: Influence of other blood cells, calcium, and aspirin - Frelinger, 3rd, Andrew L; Jakubowski, Joseph A; Li, Youfu; Barnard, Marc R; Fox, Marsha L; Linden, Matthew D; Sugidachi, Atsuhiro; Winters, Kenneth J; Furman, Mark I; Michelson, Alan D (Thrombosis and haemostasis, 2007)
The novel thienopyridine prodrug prasugrel, a platelet P2Y(12) ADP receptor antagonist, requires in vivo metabolism for activity. Although pharmacological data have been collected on the effects of prasugrel on platelet aggregation, there are few data on the direct effects of the prasugrel's active metabolite, R-138727, on other aspects of platelet function. Here we examined the effects of R-138727 on thrombo-inflammatory markers of platelet activation, and the possible modulatory effects of other blood cells, calcium, and aspirin. Blood (PPACK or citrate anticoagulated) from healthy donors pre- and post-aspirin was incubated with R-138727 and the response to ADP assessed in whole blood or platelet-rich plasma (PRP) by aggregometry and flow cytometric analysis of leukocyte-platelet aggregates, platelet surface P-selectin, and GPIIb-IIIa activation. Low-micromolar concentrations of R-138727 resulted in a rapid and consistent inhibition of these ADP-stimulated thrombo-inflammatory markers. These rapid kinetics required physiological calcium levels, but were largely unaffected by aspirin. Lower IC(50) values in whole blood relative to PRP suggested that other blood cells affect ADP-induced platelet activation and hence the net inhibition by R-138727. R-138727 did not inhibit P2Y(12)-mediated ADP-induced shape change, even at concentrations that completely inhibited platelet aggregation, confirming the specificity of R-138727 for P2Y(12). In conclusion, R-138727, the active metabolite of prasugrel, results in rapid, potent, consistent, and selective inhibition of P2Y(12)-mediated up-regulation of thrombo-inflammatory markers of platelet activation. This inhibition is enhanced in the presence other blood cells and calcium, but not aspirin.